Exploring Lymphangioma: A Synthesis of the Literature and Clinical Perspectives - Nada Bochor; Parshotam Gera (Lymphatics)
Lymphatic malformations (LMs) are benign, congenital vascular anomalies caused by abnormal lymphangiogenesis during embryology, often presenting as fluid-filled cystic lesions. Though LMs can affect any part of the body except the brain, they primarily manifest in the head and neck or axilla regions of children. With a prevalence of approximately 1 in 4000 births, LMs are commonly diagnosed by age two, with symptoms varying based on lesion location and size. This paper reviews the classification of LMs and discusses the de Serres staging system, which aids in assessing prognosis based on lesion site. Mutations in the (PIK3CA) gene are implicated in most cases, and LMs are also associated with syndromic conditions like Turner and Noonan syndromes. They are diagnosed by ultrasound (USS) or magnetic resonance imaging (MRI), while a histologic analysis can confirm lymphatic origin. Treatment options range from conservative approaches, such as observation, to sclerotherapy, pharmacotherapy, and surgery. Sclerotherapy, particularly with agents like OK-432, bleomycin, and doxycycline, has shown significant efficacy in reducing LM size and symptoms with minimal side effects. Pharmacological therapies, such as sirolimus, that target the mTOR pathway are also increasingly being used, with a good effect on the burden of disease. While surgical excision remains a choice for symptomatic or large lesions, minimally invasive approaches are often preferred due to lower morbidity. Emerging techniques include gravity-dependent sclerotherapy, electrosclerotherapy, alpelisib, everolimus, and Wnt/β-catenin pathway stimulators (e.g., tankyrase inhibitors, porcupine inhibitors). Computational atomistic molecular dynamics (MD) and density functional tight binding (DFTB) techniques may offer an experimental approach to future therapeutic targets. This paper highlights a multidisciplinary approach to LM management, emphasising individualised treatment based on lesion characteristics and patient needs.